Examining Price Perception And The Relationships Among Its D?mens?ons Via Structural Equation Modeling: A Research On Turkish Consumers - Geçti, Fatih; PhD (British Journal of Marketing Studies, 2014)
Price is one of the most important marketplace cues that consumers use in their decision making. It is widely known that consumers react differently to price. Many researchers have noted that price has a complex structure. According to Lichtenstein et al (1993), there are multidimensional aspects of price cues and suggested several dimensions. The purpose of this study is to examine price perception and the relationships among its dimensions. In order to achieve this aim, a field research was conducted on sports shoe consumers in Turkey. 638 consumers voluntarily participated the survey. According to the findings, some of the relationships among the dimensions of price perception were significant. Besides, it was revealed that the most exploratory dimensions of price perception were value consciousness and price consciousness.